Spiritualitas Agama dan Masyarakat Modern (Eksistensi Tarekat Qadiriyah Wa Naqsyabandiyah Di Bandar Lampung) - Suhandi, Suhandi (AL-ADYAN, 2019)
As a form of increasing tendency for the spirituality of the people, Indonesia has developed a wide range of orders, among which are the Qadiriyah wa naqsyabandiyah (so that they are included in the Muktabarah order). These orders are a combination of two orders (Qadiriyah and Naqsyabandiyah) performed by Sheikh Ahmad Khatib al-Sambasi al-Jawi, The dissemination of the teachings of the Qadiriyah wa Naqsyabandiyah in the Sambas district of West Kalimantan (originally Sheikh Ahmad Khatib al-Sambasi) by his two caliphs, namely Nur al-Din Shaykh of the Philippines and Shaykh Muhammad Sa'ad the original son of Sambas. In Bandar Lampung in particular TQN was held and developed in the Way Halim Bandar Lampung at the Al-Hikmah Boarding Board Foundation led by KH. Muhammad Shobari's father. After doing research using qualitative and quantitative approach (mixed methodes design). research begins with data collection activities and ends with data analysis. In data collection activities are used Quesioner Observation, Interview, documentation and dissemination methods. Once all the required data has been collected, it is analyzed using mixed methodes design. It was further concluded that the pattern of spiritual upliftment was made by the Qadiriyah wan Naqsyabandiyah (TQN) orders led by KH. Muhammad Sobari as chair of the Al-Hikmah Way Halim Bandar Lampung Boarding Foundation is emphasizing on the aspects of fasting and fasting that is practiced on a daily and weekly and monthly basis. In addition, the moral aspect of al-karimah is also a concern that is always taught by KH. Muhammad Sobari, both through the teachings of al-hasanah (in the form of lectures and advice) and through the example of trustworthiness exemplified in everyday life. So the Qadiriyah wan Naqsyabandiyah (TQN) rules are very influential to the spiritual growth of the pilgrims.